2000
DOI: 10.1016/s0042-6989(99)00211-4
|View full text |Cite
|
Sign up to set email alerts
|

What covariance mechanisms underlie green/red equiluminance, luminance contrast sensitivity and chromatic (green/red) contrast sensitivity?

Abstract: In order to investigate the mechanisms underlying green/red equiluminance matches in human observers and their relationship to mechanisms subserving luminance and/or chromatic (green/red) contrast sensitivity, we tested 21 human subjects along these dimensions at 16 different spatial and temporal frequencies (spatial frequency, 0.25-2 c/deg; temporal frequency, 2-16 Hz) and applied factor analysis to extract mechanisms underlying the data set. The results from our factor analysis revealed separate sources of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 99 publications
1
36
0
Order By: Relevance
“…Several other researchers have used latent variable modeling techniques to isolate contrast sensitivity mechanisms (Dobkins et al, 2000;Billock & Harding, 1996;Mayer et al, 1995;Sekuler et al, 1984). Such methods have also contributed to our knowledge of the functional organization of color vision (Bimler, Kirkland & Jameson, 2004;Gunther & Dobkins, 2003;Burt, 1949;Jones, 1948) and motion perception (Morrone et al, 1999).…”
Section: Functional Organizationmentioning
confidence: 99%
“…Several other researchers have used latent variable modeling techniques to isolate contrast sensitivity mechanisms (Dobkins et al, 2000;Billock & Harding, 1996;Mayer et al, 1995;Sekuler et al, 1984). Such methods have also contributed to our knowledge of the functional organization of color vision (Bimler, Kirkland & Jameson, 2004;Gunther & Dobkins, 2003;Burt, 1949;Jones, 1948) and motion perception (Morrone et al, 1999).…”
Section: Functional Organizationmentioning
confidence: 99%
“…Peterzell and Teller (2000) examined correlations between contrast sensitivity thresholds across seven levels of spatial frequency (0.27-2.16 cpd of visual angle) of gratings that were yellow-black (i.e., monochromatic or luminance modulated) and seven levels of spatial frequency of gratings that were red-green (i.e., chromatic modulated). Using principal components analysis with a varimax rotation on the 14 threshold variables, Peterzell and Teller interpreted three principal components as representing a lower spatial-frequency monochrome channel, a higher spatial-frequency monochrome channel, and a chromatic channel (see also Dobkins, Gunther, & Peterzell, 2000). These channels plausibly correspond to the MD, ID, and BD channels, respectively, of the model of visual processing of Van Essen and Anderson (1995).…”
mentioning
confidence: 99%
“…Two flicker rates were used: 16 Hz and 20 Hz. These rates were chosen for their suitability for magnocellular processing (see, e.g., Dobkins et al, 2000) and on the basis of a pilot study in which participants found performing the HFP task to be straightforward when these rates were used. The chromatic and luminance characteristics of the display screen were measured using a Cambridge Research Systems ColorCAL colorimeter.…”
Section: Experiments 1 Methodsmentioning
confidence: 99%
“…The most straightforward approach is to match the onscreen luminance of the different components so they have the same physical luminance, as measured by a photometer (see, e.g., Chase et al, 2003;Knoblauch et al, 1991;Lehky, 2000;Ojanpää & Näsänen, 2003;Travis et al, 1990; see also Allen et al, 2002). Unfortunately, onscreen isoluminance does not guarantee that stimuli are isoluminant in either retinal images or postretinal neural responses (see, e.g., Bilodeau & Faubert, 1997; see also Cavanagh, MacLeod, & Anstis, 1987;Dobkins, Gunther, & Peterzell, 2000;Livingstone & Hubel, 1987;Metha & Mullen, 1996;von Berg, Ziebell, & Stiehl, 2002), and luminance differences may therefore be readily perceived by the observer. Consequently, an alternative approach to suppressing the processing of luminance contrasts in word recognition experiments is required.…”
mentioning
confidence: 99%
See 1 more Smart Citation